IMPROVING THE XI GRADE STUDENTS’ SPEAKING ABILITY BY USING TECHNOLOGY AT SMK PERIKANAN DAN KELAUTAN PUGER - Alfianti, Desi (LP2M STAI AL-UTSMANI BONDOWOSO, 2023)
This research is conducted to improve the XI grade students’ speaking ability at SMK Perikanan dan Kelautan Puger through the use of technology. The technology used in this research is in the form of web pages (houzz.com, cooksmarts.com, walmart.com, herbmarket.in, versus.com) and webcam. It is used as a learning media to acquire speaking skill. In addition, web pages provides contextual learning for the students and webcam gives students opportunity to perform public speaking. The participants of the research are the students of XI APHPi (Agribisnis Pengolahan Hasil Perikanan) at SMK Perikanan dan Kelautan Puger. The result of the research shows that the percentage of the students who got score 75 or more in the writing test increased from 29% (in preliminary study) to 76 % (at the end of the research). In conclusion, the use of technology can improve the XI grade students’ speaking ability at SMK Perikanan dan Kelautan Puger. Therefore, it is suggested to the English teacher to use technology as instructional media in teaching descriptive text writing.